2020
DOI: 10.1021/acs.chemmater.0c02817
|View full text |Cite
|
Sign up to set email alerts
|

Seeded Growth Combined with Cation Exchange for the Synthesis of Anisotropic Cu2–xS/ZnS, Cu2–xS, and CuInS2 Nanorods

Abstract: Colloidal copper­(I) sulfide (Cu2–x S) nanocrystals (NCs) have attracted much attention for a wide range of applications because of their unique optoelectronic properties, driving scientists to explore the potential of using Cu2–x S NCs as seeds in the synthesis of heteronanocrystals to achieve new multifunctional materials. Herein, we developed a multistep synthesis strategy toward Cu2–x S/ZnS heteronanorods. The Janus-type Cu2–x S/ZnS heteronanorods are obtained by the injection of hexagonal high-chalcocite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 100 publications
1
24
0
Order By: Relevance
“…It is, however, possible that the Cu 2 –x S seed NCs undergo a structural reconstruction after the cation-exchange step and prior to the onset of the epitaxial growth of CuInS 2 , similar to previous observations on the heteroepitaxial growth of wurtzite ZnS on high-chalcocite Cu 2 S seed NCs. 30 Therefore, the unambiguous identification of the crystallographic nature of the facets where the CuInS 2 formation starts ( i.e ., those where the initial Cu + for In 3+ cation exchange occurs) would require advanced high-resolution TEM studies of the early stage samples (such as those shown in Figure 2 ). This is, however, precluded by the high electron beam sensitivity of these samples, which contain higher amounts of unreacted precursors that were not completely eliminated by the washing procedures (see discussion above).…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is, however, possible that the Cu 2 –x S seed NCs undergo a structural reconstruction after the cation-exchange step and prior to the onset of the epitaxial growth of CuInS 2 , similar to previous observations on the heteroepitaxial growth of wurtzite ZnS on high-chalcocite Cu 2 S seed NCs. 30 Therefore, the unambiguous identification of the crystallographic nature of the facets where the CuInS 2 formation starts ( i.e ., those where the initial Cu + for In 3+ cation exchange occurs) would require advanced high-resolution TEM studies of the early stage samples (such as those shown in Figure 2 ). This is, however, precluded by the high electron beam sensitivity of these samples, which contain higher amounts of unreacted precursors that were not completely eliminated by the washing procedures (see discussion above).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Copper chalcogenide-based HNCs with different compositions ( viz . Cu 2 –x S/ZnS, 25 30 Cu 2 –x S/MnS, 31 Cu 2 –x S/CdS, 32 Cu 2 –x S/PbS, 33 Cu 2 –x S/In 2 S 3 , 34 , 35 Cu 2 –x S/CuInS 2 , 36 46 CuInS 2 /ZnS, 47 , 48 CuInSe 2 /CuInS 2 49 ) have been obtained by several synthetic strategies, but the degree of control over these nanomaterials is still lagging behind that achieved for the prototypical Cd- and Pb-containing HNCs, despite many important advances in recent years. Owing to the high mobility and low-charge of Cu + , postsynthetic cation exchange reactions have been extensively used to successfully obtain a variety of copper chalcogenide-based (H)NCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Up to now, some commonly used surfactants include, polyvinylpyrrolidone (PVP), [46,110,111] cetrimonium bromide (CTAB), [112][113][114][115] polyStyrene (PS), [116,117] trimethoxyhexadecylsilane (C 18 TMS), [118] and trioctylphosphine (TOP). [119] For example, a chemical reduction method was previously used to synthesize hydrophilic Fe 3 O 4 -Au Janus nanoparticles, where PVP was used to regulate the assembly manner of Fe 3 O 4 and Au nanoparticles (Figure 6D). [120] This was because PVP had a strong affinity for precious metals such that Au NPs would preferentially nucleate on the surface of PVP-modified Fe 3 O 4 nanoparticles and form asymmetric morphology.…”
Section: Seed-mediated Growthmentioning
confidence: 99%